Atypical chest pain with non-specific ST changes: an incidental finding of myocardial bridge without flow limiting coronary lesion - Saha, Somesh; Guha Roy, Aakash; Mondal, Ritwick (International Journal of Research in Medical Sciences, 2023)
Myocardial bridging is a developmental anomaly characterized by intramural course of a short segment of epicardial coronary artery which mostly remains silent in the initial few decades of life. A 42 years old male non diabetic, hypertensive on single regime therapy presented with atypical chest pain for the last two hours. Serial 12 lead ECGs on an interval of half-hour showing nonspecific dynamic ST changes in lead II, III and aVF suggesting of inferior wall changes with negative bio markers like troponin-T and troponin-I. Coronary angiography reveals myocardial bridge in mid segment of left anterior descending artery (LAD). Considering superficial type of bridging in this case, a conservative management strategy was planned accordingly. Physicians should be more vigilant on possibilities of underlying myocardial bridging as a major differential in emergency scenarios with low suspicion of atherosclerosis but with a picture equivalent to acute coronary syndrome (ACS). Myocardial bridge carries a wide array of complications depending on variabilities like depth of tunnelling, collapsibility, loss of wall sheer stress and vasospastic changes. Hence it needs to be promptly diagnosed with immediate treatment.